PERFORMANCE EVALUATION FROM AN ISLAMIC PERSPECTIVE - Fontaine, Rodrigue; Oziev, Gapur (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
PERFORMANCE EVALUATIONFROM AN ISLAMIC PERSPECTIVE